2019
DOI: 10.3390/lubricants7070057
|View full text |Cite
|
Sign up to set email alerts
|

Solid Lubrication with MoS2: A Review

Abstract: Molybdenum disulfide (MoS2) is one of the most broadly utilized solid lubricants with a wide range of applications, including but not limited to those in the aerospace/space industry. Here we present a focused review of solid lubrication with MoS2 by highlighting its structure, synthesis, applications and the fundamental mechanisms underlying its lubricative properties, together with a discussion of their environmental and temperature dependence. An effort is made to cover the main theoretical and experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
213
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 387 publications
(246 citation statements)
references
References 206 publications
(401 reference statements)
6
213
0
3
Order By: Relevance
“…For the bronze bearings (Br, brown color series in Fig. 6), we found that the addition of graphite (BrGr) slightly improved tribological performance, whereas significant CoF reduction was achieved by adding molybdenum disulfide (MoS 2 -BrMo), as expected [25][26][27]. The two BrMo systems consistently exhibited remarkable running-in behavior, with a drop in the CoF at 20 rpm from 0.35 to below 0.1 within 8 h of operation in the case of BrMo-low.…”
Section: Coefficient Of Friction Resultssupporting
confidence: 63%
“…For the bronze bearings (Br, brown color series in Fig. 6), we found that the addition of graphite (BrGr) slightly improved tribological performance, whereas significant CoF reduction was achieved by adding molybdenum disulfide (MoS 2 -BrMo), as expected [25][26][27]. The two BrMo systems consistently exhibited remarkable running-in behavior, with a drop in the CoF at 20 rpm from 0.35 to below 0.1 within 8 h of operation in the case of BrMo-low.…”
Section: Coefficient Of Friction Resultssupporting
confidence: 63%
“…Its main attractive features are the nonzero bandgap, layer‐dependent bandgap tunability, easy and versatile functionalization, tailor‐made morphologies, etc. MoS 2 history is quite deep rooted with society; its scientific study and technical uses started since the ancient times . These developments are shown in Figure .…”
Section: Introduction To Mos2mentioning
confidence: 99%
“…Due to its lamellar shape made of individual atomically thin planes that can easily slide against each other [ 36 ], molybdenum disulphide (MoS 2 ) has been successfully used as a solid lubricant. MoS 2 can work, alone or with other additives, in different environments, such as: polymeric composites based on PEEK [ 37 , 38 ], ABS [ 39 ], PI [ 40 ] and PA [ 19 , 41 , 42 , 43 , 44 ]; liquid lubricants [ 45 , 46 , 47 ] or coatings [ 48 , 49 , 50 ], showing promising results in terms of improving friction coefficient and wear rate.…”
Section: Introductionmentioning
confidence: 99%